Intellectual property and sustainable development goals (SDGs): Driver of innovation or obstacle to progress? An analysis of recent global literature - De la Torre Llamas, Jonatan Alexis; Llamas Félix, Blanca Isabel; González García, Frida Merlina; López-Robles, José Ricardo (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. The objective is to analyze the relationship between intellectual property and the Sustainable Development Goals (SDGs) from the academic, scientific, and business perspectives indexed in Scopus to assess how intellectual property can boost or limit the achievement of the SDGs. Design/Methodology/Approach. The first research stage analyzes their performance and impact, while the second stage involves scientific mapping of the publications identified for both. This allows for studying the initial state of the topics from a common perspective to identify the relevant agents and issues in a given period. Results/Discussion. They show hierarchical and cross-cutting relationships between the clusters and highlight the centrality of the economic and regulatory approach, the relevance of environmental management and governance, and the growing role of digitization and the green economy. The thematic mapping offers a structured view of current knowledge and provides a strategic framework to guide future research and policy in the intersection between intellectual property and sustainable development. Conclusions. The analysis of the groups or clusters identified in recent literature reveals that this field of study is configured as an interdisciplinary, complex, and dynamic system, where intellectual property acts as an articulating axis of structural debates, practical applications, and emerging challenges. Originality/Value. The holistic approach to the intersection between the two concepts in various fields shows that while intellectual property can drive innovation, it can also hinder access to key technologies for developing countries. The analysis offers a crucial perspective for rethinking public policy and proposes aligning intellectual property protection with sustainability and social inclusion principles.